Characterization and optimization of biodegradable chitosan-sago based films for food packaging - Muhidin, Fadzillah (2016)
Petroleum based plastics have been used in many applications especially in food packaging industries for decades. These plastics are favorably used because they are cheaper and easy to develop yet the materials are high in toxic and nonbiodegradable. The accumulations of these plastics wastes have increased every year, reaching billions of tons undegraded and untreated plastics thus contributing to great environmental pollution. An alternative method of producing biodegradable plastics made from natural and renewable materials was developed in order to counter the environmental pollution issue. This research focused on the development and characterization of chitosan and sago biodegradable films incorporated with glycerol, sorbitol and lemongrass oil. The relationships between all components in the film formulations were studied and the optimization process using response surface methodology (RSM) and analysis of variance technique (ANOVA) were carried out. The chitosan-sago based films were characterized through various analysis, for instance, scanning electron microscopy was used for morphological study of the chitosan-sago films. Meanwhile, the resulting Fourier transform infrared spectra validated the functional groups interactions between components in the films. The antimicrobial susceptibility assay had efficiently inhibited the growth of Escherichia coli microbes, through the incorporations of lemongrass essential oil using agar and broth dilution method. Furthermore, the chitosan-sago blend formulations were analyzed using central composite design (CCD), RSM and ANOVA techniques, in order to investigate the interactions between process variables and the resulting film properties such as the water vapor permeability (WVP), water solubility (WS), tensile strength (TS), elastic modulus (EM) and elongation at break (EAB). The data fitting from RSM and ANOVA indicated that the quadratic model used in CCD and the variables-response interactions was significant (p<0.05) with the values for the coefficient of determinations, R2 of 0.9037, 0.9435, 0.8717, 0.8733, and 0.8711 for WVP, WS, TS, EM and EAB, respectively. The independent variables of chitosan and sago blend significantly increased the WVP, WS, TS and EM values of chitosansago films while glycerol, sorbitol and lemongrass oil decreased the WVP, TS and EM values. The addition of glycerol and sorbitol increased the values of EAB of chitosan-sago based films and the addition of lemongrass oil exhibited an increased in WS values. An optimum set of film formulations was generated in this research; 100 wt.% chitosan/sago, 25 wt.% glycerol/sorbitol and 0.5 wt.% lemongrass oil has yielded an optimum response of 7.637x10-11 g/Pa.s.m2 for WVP, 208.407 MPa for TS, 4.329x105 MPa for EM, and 17.682 % for EA, with an overall desirability of 0.793. The resulted optimum values were compared between current thin plastic films and from other researchers, thus indicating that the chitosan-sago based films developed in this study were adequate and potentially met the requirements for food packaging films properties.